Phantom-based multimodal interactions for medical education and training the Munich knee joint simulator. - Riener, R.
Simulation environments based on virtual reality technologies can support medical education and training. In this paper, the novel approach of an "interactive phantom" is presented that allows a realistic display of haptic contact information typically generated when touching and moving human organs or segments. The key idea of the haptic interface is to attach passive phantom objects to a mechanical actuator. The phantoms look and feel as real anatomical objects. Additional visualization of internal anatomical and physiological information and sound generated during the interaction with the phantom yield a multimodal approach that can increase performance, didactic value, and immersion into the virtual environment. Compared to classical approaches, this multimodal display is convenient to use, provides realistic tactile properties, and can be partly adjusted to different, e.g., pathological properties. The interactive phantom is exemplified by a virtual human knee joint that can support orthopedic education, especially for the training of clinical knee joint evaluation. It is suggested that the technical principle can be transferred to many other fields of medical education and training such as obstetrics and dentistry.
Keywords: Munich knee joint simulator; VR; Acoustic display; Animation; Biomechanics; Clinical knee joint evaluation; Dentistry; Didactic value; Graphical display; Haptic contact information; Internal anatomical information; Mechanical actuator; Medical education; Medical training; Multimodal display; Multimodal sound approach; Obstetrics; Orthopedic education; Pathological properties; Phantom-based multimodal interaction; Physiological information; Realistic tactile properties; Robotics; Virtual human knee joint; Virtual reality technologies